Do Regional Election and Presidential Election Affect Stock Exchange? An Event Study in the Indonesian Stock Exchange - Khanifah Khanifah; Agus Triyani; Suhita Whini Setyahuni (Universitas Medan Area, 2021)
The 2018 simultaneous regional election in Indonesia is something new in the events of democratic politics in Indonesia. The events of the 2018 simultaneous regional election is one of the important events in 2018 that can cause a reaction of capital market to these events. This study aims to examine how the capital market reacts to the simultaneous regional elections in 2018 and presidential elections in 2019, by looking at the differences in the preceding and following periods based on 2 variables, namely abnormal return and trading volume activity. The sample in this study were 30 companies listed in the Indonesian Stock Exchange during 30 periods from February through July 2018. Research Methode This study used an event study. One paired samples T test was used as a technique analysis. The means of each variable within eleven days period was compared. The period of observation is five days before the event, five days after the event, and one day on event day. Based on the results of the parametric statistical calculations, the paired sample t-test showed that there was no difference between the level of abnormal returns before and after the 2018 simultaneous regional elections. On the other hand, there was a difference between trading volume of activity before and after the 2018 simultaneous regional elections.